Large Language Model e sistema di giustizia amministrativa. Prime riflessioni sul ruolo del giudice amministrativo - Margherita Interlandi (Democrazia e Diritti Sociali)
This paper investigates the impact of LLM technology on the administrative justice system from the perspective of the role of the judge, i.e. the subject who is called upon to interact with such systems and who is the one most exposed to the risk of substitution by the machine. The choice of this profile moves from two considerations. The first concerns the awareness that administrative jurisprudence has played a fundamentally important social role due to its valuable contribution to developing a more democratic administrative law. Secondly, dwelling on the role of the judge allows us to contextualise the reflection by taking into account the debate that agitates the doctrine, which has long been committed to analysing some significant themes such as the separation of powers, the plurality of jurisdictions, the excessive creativity of administrative jurisprudence, and Full Jurisdiction. Therefore, after briefly outlining the peculiarities of the functions of the administrative judge, we will dwell on the possible implications that could derive from using AI-based technology, with specific reference to the constitutional profiles that inform due process.